(untitled) (Nóema, 2019)
Extract from the italian translation of "Critique of Dialectical Reason Volume 2: The Intelligibility of History" by Jean-Paul Sartre ("Critica della ragione dialettica, Tomo II: L’intelligibilità della storia", italian translation by F. Cambria, Christian Marinotti Edizioni, Milano 2006, pp. 409-426). Italian translation French text